A Rational Designed PslG With Normal Biofilm Hydrolysis and Enhanced Resistance to Trypsin-Like Protease Digestion - Su, Tiantian; He, Jing; Li, Ningna; Liu, Shiheng; Xu, Sujuan; Gu, Lichuan (Frontiers in Microbiology, 2020)
PslG has become a promising candidate for biofilm treatment due to its ability to inhibit and disperse biofilms of Pseudomonas aeruginosa at nanomolar concentrations. However, as a protein, the enzyme activity of PslG can be restricted by the ubiquitous proteases (of which trypsin-like serine proteases are a major group) secreted by human cells. Here, through LC-MS/MS and structural analysis, we generate a double mutant (K286A/K433S) of PslG with greatly enhanced trypsin resistance. IC50 (the concentration of trypsin that can degrade 50% of protein in 30 min at 37C) of PslGK286A/K433S increases from 0.028 mg mL-1 of the wild type PslG to about 0.283 mg mL-1. In addition, biofilm inhibition experiments showed that the activity of PslGK286A/K433S was significantly higher than that of wild type PslG when treated with trypsin. Our results indicate that PslGK286A/K433S can serve as a better biofilm inhibitor than the wild type PslG in clinical use where trypsin-like proteases continuously exist.